Brave cult member, runaway, captive, starlet, victim, sex symbol, justice seeker - McGowan, Rose 1973- (HarperOne, an imprint of HarperCollins Publishers, 2018)
The surprising and captivating memoir and radical manifesto of one of the most controversial women in Hollywood--actress, activist, musician, director, and all-around feminist badass Rose McGowan